Counterpoint in the music classroom: Creating an environment of resilience with peer mentoring and LGBTQIA+ students. (November 2020) - Goodrich, Andrew
LGBTQIA+ (lesbian, gay, bisexual, transgender, queer, intersex, asexual) students face significant challenges that include peer harassment and health risks surpassing those of students who do not identify as being gay. Learning environments that include peer mentoring promote resilience and help LGBTQIA+ students gain a sense of well-being. Researchers in music education have recently begun to explore the various complexities that exist in the recognition of sexual orientation in the music classroom, yet research on how peer mentoring assists LGBTQIA+ students with resilience is noticeably absent. Drawing upon available educational research, the social-ecological framework of resilience served as the theoretical framework with how teachers can work with LGBTQIA+ students to become resilient through the process of peer mentoring. Five themes surfaced while conducting this review: the necessity of (a) setting the foundation for peer mentoring, (b) creating safe spaces, (c) encouraging socialization, (d) establishing leadership and identity, and (e) acknowledging intersectionality. Peer mentoring contributes to student well-being and positive sexual identity for LGBTQIA+ students. Salient concepts found in the literature can aid LGBTQIA+ students in the music classroom and inform future research in music education by portraying ways music teachers can use peer mentoring to create an environment of resilience for LGBTQIA+ students.